Cryptography using Laplace transform for the Serbian language - Mirković, Tatjana; Ćirović, Nataša (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: In this paper authors develop a new mathematical method for cryptography. The procedure was performed for messages written in the Serbian language, which consists of 30 phonemes. Methods: The standard expansion of the inverse trigonometric function in a Taylor series was used. The Laplace transform was applied to encrypt the plaintext, while the corresponding inverse Laplace transform was used for decryption. Results: A new cryptographic algorithm has been written to encrypt and decrypt a text message written in Serbian letters. Conclusion: In the paper the authors presented a new algorithm in which the Laplace transform was used for the encryption and description of a message. The message is written in Serbian in Cyrillic letters.